Bank 4. 0 : banking everywhere, never at a bank - King, Brett (John Wiley & Sons, Incorporated, 2018)
The future of banking is already here-are you ready' Bank 4.0 explores the radical transformation already taking place in banking, and follows it to its logical conclusion. What will banking look like in 30 years' 50 years' The world's best banks have been forced to adapt to changing consumer behaviors; regulators are rethinking friction, licensing and regulation; Fintech start-ups and tech giants are redefining how banking fits in the daily life of consumers. To survive, banks are having to develop new capabilities, new jobs and new skills. The future of banking is not just about new thinking around value stores, payment and credit utility-it's embedded in voice-based smart assistants like Alexa and Siri and soon smart glasses which will guide you on daily spending and money decisions. The coming Bank 4.0 era is one where either your bank is embedded in your world via tech, or it no longer exists. In this final volume in Brett King's BANK series, we explore the future of banks amidst the evolution of technology and discover a revolution already at work. From re-engineered banking systems, to selfie-pay and self-driving cars, Bank 4.0 proves that we're not on Wall Street anymore. Bank 4.0 will help you: -Understand the historical precedents that flag a fundamental rethinking in banking -Discover low-friction, technology experiences that undermine the products we sell today -Think through the evolution of identity, value and assets as cash and cards become obsolete -Learn how Fintech and tech "disruptors" are using behaviour, psychology and technology to reshape the economics of banking -Examine the ways in which blockchain, A.I., augmented reality and other leading-edge tech are the real building blocks of the future of banking systems If you look at individual technologies or startups disrupting the space, you might miss the biggest signposts to the future and you might also miss that most of we've learned about banking the last 700 years just isn't useful. When the biggest bank in the world isn't any of the names you'd expect, when branch networks are a burden not an asset, and when advice is the domain of Artificial Intelligence, we may very well have to start from scratch. Bank 4.0 takes you to a world where banking will be instant, smart and ubiquitous, and where you'll have to adapt faster than ever before just to survive. Welcome to the future